Shovelomics: high throughput phenotyping of maize (Zea mays L.) root architecture in the field - Trachsel, Samuel; Kaeppler, Shawn M; Brown, Kathleen M; Lynch, Jonathan P (Plant and soil, 2011)
We present a method to visually score 10 root architectural traits of the root crown of an adult maize plant in the field in a few minutes. Phenotypic profiling of three recombinant inbred line (RIL) populations of maize (Zea mays L.; B73xMo17, Oh43xW64a, Ny821xH99) was conducted in 2008 in a silt loam soil in Pennsylvania and in a sandy soil in Wisconsin, and again in 2009 in Pennsylvania. Numbers, angles and branching pattern of crown and brace roots were assessed visually at flowering. Depending on the soil type in which plants were grown, sample processing took from three (sand) to 8 min (silt-loam). Visual measurement of the root crown required 2 min per sample irrespective of the environment. Visual scoring of root crowns gave a reliable estimation of values for root architectural traits as indicated by high correlations between measured and visually scored trait values for numbers (r ² = 0.46-0.97), angles (r ² = 0.66-0.76), and branching (r ² = 0.54-0.88) of brace and crown roots. Based on the visual evaluation of root crown traits it was possible to discriminate between populations. RILs derived from the cross NY821 x H99 generally had the greatest number of roots, the highest branching density and the most shallow root angles, while inbred lines from the cross between OH43 x W64a generally had the steepest root angles. The ranking of genotypes remained the same across environments, emphasizing the suitability of the method to evaluate genotypes across environments. Scoring of brace roots was better correlated with the actual measurements compared to crown roots. The visual evaluation of root architecture will be a valuable tool in tailoring crop root systems to specific environments.